Speeches and journeys in the corporeality of time-space [Discursos y recorridos en la corporalidad del tiempo-espacio] (2019)
"The philosophy of Kant reveals, as he expressed it, a ""awakening of the Dogmatic Dream"", which is based on a copernicanic twist in Western philosophy. This article displays some reflections on this philosophical turn that can be understood in the link between body, time-space and language, where the poetic formulas: the time is out of its hinges, I am another and the deepest of the human is the skin, allow To open a comprehensive panorama of the problem of reason, understanding and sensibility of Kantian transcendental aesthetics. Therefore, the Copernicanic Giro advocated by Kant is guided by his premise according to which ""we only know of things what we ourselves put in them"" (Critique of Pure Reason), deriving in the problem on the conditions of possibility of knowledge Expressed in the relationship between body, time-space and language. From this last point of view, there is an analysis of the schematism Kantian and the Diagramatismo Foucault in what could be thought of as what beats in the corporeality of an inhabiting the world in what we project of ourselves in the margins of the Language. © 2019 Pontificia Universidade Catolica do Parana."